Optimization methods of replenishment of material base of agriculture (Journal of Economic Research & Business Administration, 2016)
The article discusses the current state of agricultural production, inadequatetechnical security of rural producers, analyzed the development oftechnical equipment of rural enterprises, made a calculation of the requiredcomposition of technical base of agricultural production by applying a regressionequation on the imputation principle of optimization of structure oftechnical resources. Also in the ways of the agroservice enterprises, wherethe concentration of modern machines used to perform time-consuming andresponsible work that is not able to carry out individual farms.
Keywords: agricultural production; technical resources; security; physical infrastructure; agricultural enterprises; efficiency; optimization; development; improvement.